Mapping the Landscape of ICT Integration in Education: A Systematic review of Literature - Baako, Issah; Osei, Eric Opoku; Abroampa, Winston Kwame (Indonesian Journal of Education and Social Sciences, 2025)
The integration of Information and Communication Technologies (ICT) in education has received considerable attention and interest in the field of education. However, there is a lack of systematic literature reviews that explore the visibility and bibliometric portrait of ICT integration. This article aims to address this knowledge gap by conducting a comprehensive review of existing literature, focusing specifically on the utilization of ICT within slum community schools. A total of 71 relevant articles were identified and subjected to quality evaluation and review consideration. The study follows the Tripartite Model for Systematic Literature Review by Daniel and Harland (2017). The review focuses on articles published between 2012 and 2022 to understand the current state of research on ICT for Education (ICT4E) and its impact on teaching and learning. The examination reveals a scarcity of literature on the influence of inadequate ICT resources on teachers' beliefs and actual utilization of ICT in educational settings. Additionally, there is a lack of research exploring how teachers and students overcome technological obstacles within classrooms. These gaps emphasize the need for further investigation into the implementation of ICT4E in Ghanaian public schools. This review is part of an ongoing research that commenced in 2021 and aims to provide a literature map of ICT integration in education, with a focus on the past decade.